Service Quality as Drivers of Customer Loyalty and Intention to Switch: Modeling the Mediating Effect of Customer Satisfation - Zailin Zainal Ariffin; Azizul Yadi Yaakop; Norsuhada Isa; Siti Sarah Omar; Nor Khasimah Aliman; Ramraini Ali Hassan (2018)
The following study examines relationship of service quality, customer satisfaction, customer loyalty and consumers’ intentions to switch among finance and insurances consumers in Klang Valley area. Although many researchers have studied of service quality, customer satisfaction, customer loyalty and intention to switch, limited studies explore customer satisfaction as mediating role in the model. The present study proposes SERVQUAL model as indicator to determine the customer satisfaction among finance and insurances consumer. Stratified random sampling technique will be employed in the present study. Data collected also will be analyzed using the Smart PLS (Partial Least Square) to answer the hypothesis. It is believed that the mediating role of customer satisfaction is a promising area to explore and the potential to provide significant benefit to the finance and insurance institution.